Electrochemical Performances of Tin Oxide-Mesoporous Carbon Composites for Lithium Ion Battery Application - Le, Hang T. T.; Nguyen, Yen Thi; Dung, Dang Viet Anh; Park, Chan-Jin (Old Journal, 2019)
A composite of tin oxide (SnO2) and mesoporous carbon (namely HCMK3) was synthesized and investigated as anode active material for rechargeable lithium ion batteries. Nanostructured composite was prepared by incipient wetness impregnation technique in combination with a chemical reduction method. The resultant composite was 800 nm-nanorods, which were composed of discrete SnO2 nanocrystals with a size of about 3 nm filling both inside and outside the mesopores of HCMK3 carbon. The obtained electrochemical results demonstrated that owing to its novel architecture, the composite electrode showed outstanding reversible capacity, excellent rate capability, and superior long-term cycling performance. Even at a high charge-discharge rate of 1C, a high reversible capacity of 398.6 mAh g-1 was achieved after 500 cycles.